Pengaruh Gaya Hidup Dan Promosi Online Terhadap Keputusan Pembelian Konsumen Pada Produk Eiger Di Kota Langsa - Hermawan, Ditiya; Amilia, Suri; Ardiyanti, Dyah Ayu (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to determine the effect of lifestyle, online promotion on consumer purchasing decisions on Eiger products in Langsa City. The sample used in this study amounted to 96 respondents. The data analysis method used multiple linear regression analysis, t test, F test, and coefficient of determination test. The regression equation in this study is Y = 4.219 + 0.330X1 + 0.294X2. Lifestyle has a significant effect on purchasing decisions on Eiger products in Langsa City as evidenced by the t test, where the t sig value is obtained. 0.023 < 0.05. Online promotion has a significant effect on purchasing decisions on Eiger products in Langsa City as evidenced by the t test, where the t sig value is obtained. 0.035 < 0.05. Lifestyle, online promotion and brand trust simultaneously have a significant effect on purchasing decisions on Eiger products in Langsa City as evidenced by the F test, where the F sig value is obtained. 0.000 < 0.05. From the coefficient of determination test, it is known that the Adjusted R Square value is 0.604. That is, the variables of lifestyle, online promotion and brand trust affect purchasing decisions on Eiger products in Langsa City by 60.4%, while the remaining 39.6% is influenced by other variables outside this research model.